Construction of a Functional Single-Chain Variable Fragment Antibody against Hemagglutinin from Porphyromonas gingivalis - Shibata, Yasuko (American Society for Microbiology, 1998)
Hemagglutinin is a major glycoprotein of Porphyromonas gingivalis vesicles and likely confers the ability to adsorb and penetrate into host tissue cells. To protect this bacterial invasion, murine monoclonal antibody (MAb) Pg-vc, which inhibited the hemagglutinating activity, was prepared by using P. gingivalis vesicles as an antigen. Western blot analysis revealed that when both MAb Pg-vc and anti-HA-Ag2 antibody raised against the P. gingivalis hemagglutinin adhesin (M. Deslauriers and C. Mouton, Infect. Immun. 60:2791–2799, 1992) were allowed to react with protein blots from P. gingivalis vesicles, a superimposable profile was observed. To obtain a recombinant antibody, cDNAs coding for the variable domains of the L and H chains of MAb Pg-vc were cloned by PCR, and a plasmid specifying a single-chain variable fragment (ScFv) was constructed. Following transformation of Escherichia coli cells, a recombinant ScFv protein was successfully expressed. The immunological properties of this protein were identical to those of the parental murine MAb, specifically recognizing the two proteins (43 and 49 kDa) originating from P. gingivalis vesicles. In addition, the ScFv antibody inhibited the P. gingivalis vesicle-associated hemagglutinating activity. The amino acid sequences deduced from nucleotide sequencing experiments confirmed that variable heavy-chain and variable light-chain regions belonged to VH1 and Vκ12/13 families, respectively. Since the expression system used in this study can readily provide large quantities of single-chain recombinant antibody, it may be a useful in developing a therapeutic agent for passive immunization in humans.